High-performance aerogel plate and preparation method thereof
By replacing traditional binders with hydrophobic agents and designing multi-layer hydrophobic layers, combining silica with alumina aerogel, the problem of degradation of fire resistance at high temperatures is solved, achieving high performance and long-term Aerogel board with a lifetime, suitable for high temperature environments.
Patent Information
- Application Number
- CN202411233677.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-03
AI Technical Summary
When used in high-temperature environments, existing aerogel boards are prone to deterioration of fire resistance due to latex powder blocking holes, and it is difficult to maintain waterproof performance, which affects service life.
Hydrophobic agents are used to replace traditional polymer binders, and high-performance aerogel boards are prepared through rotary spraying and multi-layer pressing processes. Multi-layer hydrophobic layers are designed to resist the invasion of water vapor, combined with silica and alumina aerogel combination. Improve the overall performance of the material.
It significantly improves the strength and overall performance of the aerogel plate, extends its service life, is suitable for use in high temperature environments, and has excellent hydrophobic and fire-resistant properties, and is suitable for boiler insulation and battery energy storage and other fields.
Smart Images

Figure CN119241204A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal insulation materials, and in particular to a high-performance aerogel board and a preparation method thereof. Background Art
[0002] Aerogel is a material with a nanoporous structure, extremely low density, high specific surface area, and unique physical and chemical properties. Due to its unique properties, aerogel is widely used in thermal insulation, environmental management, sound insulation and noise reduction, energy storage, etc. The main products of aerogel applications are aerogel felt and aerogel board. Both of these products overcome the problems of low strength, high brittleness, and high loss of aerogel by adding fibers and binders. Aerogel felt still has problems of high dust, high pollution, easy water seepage, and short service life during use; and the latex powder in the aerogel board is also easy to cause aerogel to block holes and reduce fire resistance, making it difficult to use at high temperatures. Summary of the invention
[0003] In view of the technical problem that the use of latex powder in existing aerogel boards easily causes aerogel pore blockage and reduced waterproof performance, the present invention provides a high-performance aerogel board and a preparation method thereof, wherein a hydrophobic agent is used to replace the traditional polymer binder, and a rotary spraying and multi-layer pressing process is used to prepare the high-performance aerogel board through low-temperature baking and shaping. Not only is the strength of the product greatly improved, but the overall performance of the board is also better, and no organic components are added to the material, which is particularly suitable for use in high temperature environments. In addition, the multi-layer hydrophobic layer is designed to effectively resist water vapor invasion, thereby greatly extending the service life of the aerogel board.
[0004] To achieve the above objectives, the present invention adopts the following technical scheme: a high-performance aerogel plate, the high-performance aerogel plate comprises a plurality of periodic structure layers consisting of an aerogel layer and a hydrophobic layer, and the mass ratio of the total aerogel layer to the total hydrophobic layer is 80-120:3-8; the aerogel layer comprises the following raw materials in parts by weight: 40-55 parts of silica aerogel powder, 10-15 parts of alumina aerogel powder, 5-15 parts of chopped fibers, 10-15 parts of titanium dioxide, and 10-20 parts of silicon carbide powder; the hydrophobic layer is made of a hydrophobic agent.
[0005] Furthermore, the particle size of the silica-alumina aerogel powder is 30 to 80 μm, and the particle size of the alumina aerogel powder is 30 to 80 μm.
[0006] Furthermore, the chopped fibers are one of glass fibers, high-silica fibers and aluminum silicate fibers; the diameter of the chopped fibers is 3 to 20 μm, and the length is 3 to 10 mm.
[0007] Furthermore, the titanium dioxide is rutile, the particle size of the titanium dioxide is in the range of 20 to 40 μm, and the particle size of the silicon carbide powder is in the range of 2 to 10 μm.
[0008] Furthermore, the hydrophobic agent is one of 30% sodium methyl silicate solution, 30% potassium methyl silicate solution, and polymethyltriethoxysilane.
[0009] Furthermore, the method for preparing the high-performance aerogel plate comprises the following steps:
[0010] (1) mixing silica aerogel powder, alumina aerogel powder, titanium dioxide, and silicon carbide powder to obtain a mixture;
[0011] (2) adding chopped fibers to the mixture obtained in step (1) and mixing to obtain a premix;
[0012] (3) laying a layer of the premix obtained in step (2) with a thickness of 3 to 5 mm in a mold to form an aerogel layer; spraying a layer of a hydrophobic agent on the aerogel layer to form a hydrophobic layer; repeatedly laying the premix and then spraying the hydrophobic agent to sequentially prepare an aerogel layer and a hydrophobic layer until the product thickness is reached, and then performing pressure molding to obtain a prefabricated board;
[0013] (4) taking out the prefabricated board obtained in step (3) and heating it to obtain a crude product, and processing the crude product to obtain a high-performance aerogel board.
[0014] Furthermore, in step (1), titanium dioxide, silicon carbide powder, silicon dioxide aerogel powder and alumina aerogel powder are mixed by a high-speed disperser, the dispersion speed is 800-1500 r / min, and the stirring time is 15-30 min.
[0015] Furthermore, in step (2), the mixture and the chopped fibers are mixed evenly using a high-speed disperser, the dispersion speed is 300 to 600 r / min, and the stirring time is 35 to 60 min.
[0016] Furthermore, in step (3), the pressure of the pressurizing molding is 3 to 8 MPa, and the holding time is 10 to 25 min.
[0017] Furthermore, in step (4), the heating temperature is 80 to 150° C. and the heating time is 30 to 75 minutes.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present application adopts an inorganic hydrophobic agent to replace the traditional organic binder, thereby improving the overall fireproof performance of the material; the hydrophobic agent is sprayed by a rotary spraying process in combination with a multi-layer pressing process, which not only makes the dispersion more uniform, but also increases the bonding strength, thereby solving the problem of large dosage and easy pore blocking of traditional binders, and overcoming the influence of traditional polymer binders on the performance of aerogels, and can be applied to high-temperature fields such as boiler insulation and battery energy storage;
[0020] (2) The present application adopts a rotary spraying process to spray a hydrophobic agent in combination with a multi-layer pressing process, so that the material has a multi-layer hydrophobic structure and has excellent hydrophobic properties from the inside out, which can overcome the disadvantage of aerogel material structure collapse caused by water vapor penetration and greatly extend the service life of aerogel materials;
[0021] (3) The present application adopts a compound of silica and alumina aerogels. The addition of alumina aerogel overcomes the problem that the silica aerogel is prone to structural collapse above 800°C, thereby causing material performance failure, expands the application range of the product, and can maintain good thermal insulation effect at 800-1200°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a structural schematic diagram of Example 1;
[0023] Figure 2 It is a structural schematic diagram of Comparative Example 3;
[0024] Among them, 1 is the aerogel layer; 2 is the hydrophobic layer. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] The high performance aerogel plate of this embodiment is prepared by the following steps:
[0028] (1) Add 40 parts of silica aerogel powder, 15 parts of alumina aerogel powder, 10 parts of titanium dioxide, and 10 parts of silicon carbide powder into a high-speed disperser according to the formula, stir at a dispersion speed of 1500 r / min for 15 minutes, and mix to obtain a mixture;
[0029] (2) adding 5 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersing speed of 600 r / min for 30 min, and mixing to obtain a premix;
[0030] (3) laying a layer of the premix obtained in step (2) with a thickness of 3 mm in the mold to form an aerogel layer; spraying a layer of 30% sodium methyl silicate solution on the aerogel layer to form a hydrophobic layer; repeatedly laying the premix and then spraying 30% sodium methyl silicate solution to prepare an aerogel layer and a hydrophobic layer in sequence until the product thickness reaches 15 mm, then placing it in a molding machine and maintaining the pressure at 5 MPa for 10 minutes to obtain a prefabricated board; the mass ratio of the total aerogel layer to the total hydrophobic layer is 80:5;
[0031] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 100° C. for 30 minutes to set it, thereby obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0032] Example 2
[0033] The high performance aerogel plate of this embodiment is prepared by the following steps:
[0034] (1) adding 45 parts of silica aerogel powder, 10 parts of alumina aerogel powder, 12 parts of titanium dioxide, and 13 parts of silicon carbide powder into a high-speed disperser according to the formula, stirring at a dispersion speed of 1500 r / min for 15 minutes, and mixing to obtain a mixture;
[0035] (2) adding 8 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersing speed of 600 r / min for 30 min, and mixing to obtain a premix;
[0036] (3) laying a layer of the premix obtained in step (2) with a thickness of 3 mm in the mold to form an aerogel layer; spraying a layer of 30% sodium methyl silicate solution on the aerogel layer by a rotary spraying process to form a hydrophobic layer; repeatedly laying the premix and then spraying 30% sodium methyl silicate solution to prepare an aerogel layer and a hydrophobic layer in sequence until the product thickness reaches 15 mm, then placing it in a molding machine and maintaining the pressure at 4 MPa for 12 minutes to obtain a prefabricated board; the mass ratio of the total aerogel layer to the total hydrophobic layer is 88:3;
[0037] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 120° C. for 30 min to set it, thereby obtaining a crude product, and polishing, dust-removing, cutting, and packaging the surface of the crude product to obtain a high-performance aerogel board.
[0038] Example 3
[0039] The high performance aerogel plate of this embodiment is prepared by the following steps:
[0040] (1) Add 50 parts of silica aerogel powder, 10 parts of alumina aerogel powder, 11 parts of titanium dioxide, and 13 parts of silicon carbide powder into a high-speed disperser according to the formula, stir at a dispersion speed of 1500 r / min for 15 minutes, and mix to obtain a mixture;
[0041] (2) adding 10 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersing speed of 500 r / min for 30 min, and mixing to obtain a premix;
[0042] (3) laying a layer of the premix obtained in step (2) with a thickness of 3 mm in the mold to form an aerogel layer; spraying a layer of 30% sodium methyl silicate solution on the aerogel layer by a rotary spraying process to form a hydrophobic layer; repeatedly laying the premix and then spraying 30% sodium methyl silicate solution to prepare an aerogel layer and a hydrophobic layer in sequence until the product thickness reaches 15 mm, then placing it in a molding machine and maintaining the pressure at 3 MPa for 15 minutes to obtain a prefabricated board; the mass ratio of the total aerogel layer to the total hydrophobic layer is 94:6;
[0043] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 100° C. for 30 minutes to set it, thereby obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0044] Example 4
[0045] The high performance aerogel plate of this embodiment is prepared by the following steps:
[0046] (1) Add 55 parts of silica aerogel powder, 11 parts of alumina aerogel powder, 12 parts of titanium dioxide, and 20 parts of silicon carbide powder into a high-speed disperser according to the formula, stir at a dispersion speed of 1500 r / min for 15 minutes, and mix to obtain a mixture;
[0047] (2) adding 10 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersing speed of 500 r / min for 30 min, and mixing to obtain a premix;
[0048] (3) laying a layer of the premix obtained in step (2) with a thickness of 3 mm in the mold to form an aerogel layer; spraying a layer of 30% sodium methyl silicate solution on the aerogel layer by a rotary spraying process to form a hydrophobic layer; repeatedly laying the premix and then spraying 30% sodium methyl silicate solution to prepare an aerogel layer and a hydrophobic layer in sequence until the product thickness reaches 15 mm, then placing it in a molding machine and maintaining the pressure at 8 MPa for 10 minutes to obtain a prefabricated board; the mass ratio of the total aerogel layer to the total hydrophobic layer is 108:7;
[0049] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 130° C. for 30 min to set it, and obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0050] Example 5
[0051] The high performance aerogel plate of this embodiment is prepared by the following steps:
[0052] (1) Add 50 parts of silica aerogel powder, 12 parts of alumina aerogel powder, 15 parts of titanium dioxide, and 10 parts of silicon carbide powder into a high-speed disperser according to the formula, stir at a dispersion speed of 1500 r / min for 15 minutes, and mix to obtain a mixture;
[0053] (2) adding 12 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersion speed of 400 r / min for 30 min, and mixing to obtain a premix;
[0054] (3) laying a layer of the premix obtained in step (2) with a thickness of 3 mm in the mold to form an aerogel layer; spraying a layer of 30% potassium methyl silicate solution on the aerogel layer by a rotary spraying process to form a hydrophobic layer; repeatedly laying the premix and then spraying 30% potassium methyl silicate solution to prepare an aerogel layer and a hydrophobic layer in sequence until the product thickness reaches 15 mm, then placing it in a molding machine and maintaining the pressure at 8 MPa for 12 minutes to obtain a prefabricated board; the mass ratio of the total aerogel layer to the total hydrophobic layer is 99:4;
[0055] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 110° C. for 30 min to set it, and obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0056] Example 6
[0057] The high performance aerogel plate of this embodiment is prepared by the following steps:
[0058] (1) adding 48 parts of silica aerogel powder, 13 parts of alumina aerogel powder, 11 parts of titanium dioxide, and 17 parts of silicon carbide powder into a high-speed disperser according to the formula, stirring at a dispersion speed of 1500 r / min for 15 minutes, and mixing to obtain a mixture;
[0059] (2) adding 14 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersing speed of 600 r / min for 30 min, and mixing to obtain a premix;
[0060] (3) laying a layer of the premix obtained in step (2) with a thickness of 3 mm in the mold to form an aerogel layer; spraying a layer of 30% sodium methyl silicate solution on the aerogel layer by a rotary spraying process to form a hydrophobic layer; repeatedly laying the premix and then spraying 30% sodium methyl silicate solution to prepare an aerogel layer and a hydrophobic layer in sequence until the product thickness reaches 15 mm, then placing it in a molding machine and maintaining the pressure at 5 MPa for 10 minutes to obtain a prefabricated board; the mass ratio of the total aerogel layer to the total hydrophobic layer is 103:7;
[0061] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 130° C. for 30 min to set it, and obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0062] Example 7
[0063] The high performance aerogel plate of this embodiment is prepared by the following steps:
[0064] (1) Add 52 parts of silica aerogel powder, 13 parts of alumina aerogel powder, 15 parts of titanium dioxide, and 20 parts of silicon carbide powder into a high-speed disperser according to the formula, stir at a dispersion speed of 1500 r / min for 15 minutes, and mix to obtain a mixture;
[0065] (2) adding 15 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersing speed of 600 r / min for 30 min, and mixing to obtain a premix;
[0066] (3) laying a layer of the premix obtained in step (2) with a thickness of 3 mm in the mold to form an aerogel layer; spraying a layer of polymethyltriethoxysilane on the aerogel layer by a rotary spraying process to form a hydrophobic layer; repeatedly laying the premix and then spraying 30% sodium methyl silicate solution to prepare an aerogel layer and a hydrophobic layer in sequence until the product thickness reaches 15 mm, then placing the premix in a molding machine and maintaining the pressure at 5 MPa for 14 minutes to obtain a prefabricated board; the mass ratio of the total aerogel layer to the total hydrophobic layer is 115:7;
[0067] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 130° C. for 30 min to set it, and obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0068] Example 8
[0069] The high performance aerogel plate of this embodiment is prepared by the following steps:
[0070] (1) Add 55 parts of silica aerogel powder, 15 parts of alumina aerogel powder, 15 parts of titanium dioxide, and 20 parts of silicon carbide powder into a high-speed disperser according to the formula, stir at a dispersion speed of 1500 r / min for 15 minutes, and mix to obtain a mixture;
[0071] (2) adding 15 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersion speed of 500 r / min for 30 min, and mixing to obtain a premix;
[0072] (3) laying a layer of the premix obtained in step (2) with a thickness of 3 mm in the mold to form an aerogel layer; spraying a layer of polymethyltriethoxysilane on the aerogel layer by a rotary spraying process to form a hydrophobic layer; repeatedly laying the premix and then spraying 30% sodium methyl silicate solution to prepare an aerogel layer and a hydrophobic layer in sequence until the product thickness reaches 15 mm, then placing the premix in a molding machine and maintaining the pressure at 8 MPa for 10 minutes to obtain a prefabricated board; the mass ratio of the total aerogel layer to the total hydrophobic layer is 120:8;
[0073] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 130° C. for 30 min to set it, and obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0074] The present invention designs comparative examples 1 to 3, respectively taking embodiment 6 as controls, the difference of comparative example 1 is that the aerogel plate is a structural layer composed of an aerogel layer and a hydrophobic layer; the difference between comparative example 2 and comparative example 3 is that they are prepared by a traditional aerogel plate preparation method, and the traditional adhesives used are ethylene-vinyl acetate copolymer (VAE) latex powder and VAE emulsion, respectively.
[0075] Comparative Example 1
[0076] The aerogel plate of this comparative example was prepared by the following steps:
[0077] (1) adding 48 parts of silica aerogel powder, 13 parts of alumina aerogel powder, 11 parts of titanium dioxide, and 17 parts of silicon carbide powder into a high-speed disperser according to the formula, stirring at a dispersion speed of 1500 r / min for 15 minutes, and mixing to obtain a mixture;
[0078] (2) adding 14 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersing speed of 600 r / min for 30 min, and mixing to obtain a premix;
[0079] (3) laying the premix obtained in step (2) in a mold to form an aerogel layer; spraying a layer of 30% sodium methyl silicate solution on the aerogel layer by a rotary spraying process to form a hydrophobic layer, wherein the mass ratio of the total aerogel layer to the total hydrophobic layer is 103:7; the product thickness reaches 15 cm, and then puts it into a molding machine and maintains the pressure at 5 MPa for 10 minutes to obtain a prefabricated board;
[0080] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 130° C. for 30 min to set it, and obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0081] Comparative Example 2
[0082] The aerogel plate of this comparative example was prepared by the following steps:
[0083] (1) adding 48 parts of silica aerogel powder, 13 parts of alumina aerogel powder, 11 parts of titanium dioxide, 17 parts of silicon carbide powder, and 7 parts of VAE latex powder into a high-speed disperser according to the formula, stirring at a dispersion speed of 1500 r / min for 15 minutes, and mixing to obtain a mixture;
[0084] (2) adding 14 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersing speed of 600 r / min for 30 min, and mixing to obtain a premix;
[0085] (3) spreading a layer of the premix obtained in step (2) with a thickness of 15 mm in the mold, and then placing it in a molding press, maintaining the pressure at 5 MPa for 10 minutes, to obtain a prefabricated board;
[0086] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 130° C. for 30 min to set it, and obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0087] Comparative Example 3
[0088] The aerogel plate of this comparative example was prepared by the following steps:
[0089] (1) adding 48 parts of silica aerogel powder, 13 parts of alumina aerogel powder, 11 parts of titanium dioxide, 17 parts of silicon carbide powder, and 7 parts of VAE emulsion into a high-speed disperser according to the formula, stirring at a dispersion speed of 1500 r / min for 15 minutes, and mixing to obtain a mixture;
[0090] (2) adding 14 parts of chopped fibers to the mixture obtained in step (1), stirring the mixture in a high-speed disperser at a dispersing speed of 600 r / min for 30 min, and mixing to obtain a premix;
[0091] (3) spreading a layer of the premix obtained in step (2) with a thickness of 15 mm in the mold, and then placing it in a molding press, maintaining the pressure at 5 MPa for 10 minutes, to obtain a prefabricated board;
[0092] (4) taking out the prefabricated board obtained in step (3) and placing it in an oven, heating it at 130° C. for 30 min to set it, and obtaining a crude product. The surface of the crude product is polished, dusted, cut, and packaged to obtain a high-performance aerogel board.
[0093] The performance of the products in the embodiments of the present invention and the comparative examples was tested, and the specific performances are shown in Tables 1 and 2.
[0094] Table 1 Performance results of Examples 1 to 8
[0095]
[0096] Table 2 Performance results of comparative examples 1 to 3
[0097]
[0098]
[0099] Figure 1 , Figure 2 is a schematic diagram of the structure of Example 1 and Comparative Example 3 of the present invention, Figure 1 It can be seen that the high-performance aerogel plate of Example 1 comprises a plurality of periodic structural layers consisting of an aerogel layer 1 and a hydrophobic layer 2, the hydrophobic agent is more evenly dispersed, and the bonding strength is better, and the multi-layer hydrophobic structure can overcome the disadvantage of aerogel material structure collapse caused by water vapor penetration; Figure 2 It can be seen that the binder is dispersed in the aerogel, the binder is prone to agglomeration, and the amount of binder used is large and it is easy to block pores, affecting the performance.
[0100] As can be seen from Table 1, the products of Examples 1 to 8 have low water absorption and good thermal insulation and flame retardant properties. Through the multi-layer hydrophobic structure, they can play a bonding role on the aerogel material while avoiding water vapor penetration. As can be seen from Table 2, the products of Comparative Examples 1 to 3 have high water absorption and poor thermal insulation and flame retardant properties. Comparative Examples 2 and 3 use VAE latex powder and VAE emulsion to bond aerogel materials, but they have no hydrophobic properties and are prone to collapse of the aerogel material structure due to water vapor penetration; Comparative Example 1 has only one hydrophobic layer, which has little bonding effect on the aerogel material, resulting in decreased performance.
[0101] The present invention verifies Examples 1 to 8 and Comparative Examples 1 to 3 from the perspective of thermal conductivity, water absorption, and combustion performance (A1), and the specific test method is as follows:
[0102] The thermal conductivity adopts GB / T 8484-2008 "Test method for thermal properties of building materials". The lower the thermal conductivity value, the better.
[0103] The water absorption rate adopts the method of GB / T 3810.3-2006 "Test methods for ceramic tiles Part 3: Determination of water absorption, apparent porosity, apparent relative density and bulk density". The lower the water absorption rate value, the better.
[0104] The combustion performance adopts GB 8624-2012 "Classification of Combustion Performance of Building Materials and Products". The smaller the mass loss rate value, the better, and the smaller the flame duration value, the better.
[0105] The above-mentioned specific embodiments are some specific explanations made to make the invention easier to understand. Those skilled in the art may make similar improvements without violating the connotation of the invention, so the invention is not limited by the above-disclosed specific implementations.
Claims
1. A high performance aerogel board, characterized in that: The high-performance aerogel plate comprises a plurality of periodic structure layers consisting of an aerogel layer and a hydrophobic layer, and the mass ratio of the total aerogel layer to the total hydrophobic layer is 80-120:3-8; the aerogel layer comprises the following raw materials in parts by weight: 40-55 parts of silica aerogel powder, 10-15 parts of alumina aerogel powder, 5-15 parts of chopped fibers, 10-15 parts of titanium dioxide, and 10-20 parts of silicon carbide micropowder; the hydrophobic layer is made of a hydrophobic agent.
2. The high performance aerogel plate according to claim 1, characterized in that: The particle size of the silica-alumina aerogel powder is 30-80 μm, and the particle size of the alumina aerogel powder is 30-80 μm.
3. The high performance aerogel plate according to claim 1, characterized in that: The chopped fibers are one of glass fibers, high-silica fibers and aluminum silicate fibers; the diameter of the chopped fibers is 3 to 20 μm and the length is 3 to 10 mm.
4. The high performance aerogel plate according to claim 1, characterized in that: The titanium dioxide is rutile type, the particle size of the titanium dioxide is in the range of 20 to 40 μm, and the particle size of the silicon carbide powder is in the range of 2 to 10 μm.
5. The high performance aerogel plate according to claim 1, characterized in that: The hydrophobic agent is one of 30% sodium methyl silicate solution, 30% potassium methyl silicate solution, and polymethyltriethoxysilane.
6. A method for preparing a high-performance aerogel plate according to any one of claims 1 to 5, characterized in that: The steps include: (1) mixing silica aerogel powder, alumina aerogel powder, titanium dioxide, and silicon carbide powder to obtain a mixture; (2) adding chopped fibers to the mixture obtained in step (1) and mixing to obtain a premix; (3) laying a layer of the premix obtained in step (2) with a thickness of 3 to 5 mm in a mold to form an aerogel layer; spraying a layer of a hydrophobic agent on the aerogel layer to form a hydrophobic layer; repeatedly laying the premix and then spraying the hydrophobic agent to sequentially prepare an aerogel layer and a hydrophobic layer until the product thickness is reached, and then performing pressure molding to obtain a prefabricated board; (4) taking out the prefabricated board obtained in step (3) and heating it to obtain a crude product, and processing the crude product to obtain a high-performance aerogel board.
7. The preparation method according to claim 6, characterized in that: In step (1), titanium dioxide, silicon carbide powder, silicon dioxide aerogel powder and aluminum oxide aerogel powder are mixed by a high-speed disperser, the dispersion speed is 800-1500 r / min, and the stirring time is 15-30 min.
8. The preparation method according to claim 6, characterized in that: In step (2), the mixture and the chopped fibers are mixed evenly by a high-speed disperser, the dispersion speed is 300 to 600 r / min, and the stirring time is 35 to 60 min.
9. The preparation method according to claim 6, characterized in that: In step (3), the pressure of the pressurized molding is 3 to 8 MPa, and the holding time is 10 to 25 min.
10. The preparation method according to claim 6, characterized in that: In step (4), the heating temperature is 80 to 150° C. and the heating time is 30 to 75 minutes.
Citation Information
Cited By
Aerogel modification-based solvent-free epoxy fireproof coating and preparation method thereof
CN119823628A
Aerogel-modified solvent-free epoxy fire retardant coating and preparation method thereof
CN119823628B